Gender Equality in Islamic Education: Curriculum, Pedagogy, and Media Strategies - Dudun Najmudin; Ilham Pebrian; Lia Susanti; Mulyawan Safwandy Nugraha; Nadira Salsabila (LPPM IAIN Parepare, 2025)
Gender inequality continues to shape Islamic education in Indonesia, particularly through curriculum, pedagogy, and institutional practices that reproduce patriarchal norms. This study aims to examine the conceptual foundations, challenges, and strategic frameworks for integrating gender-responsive values into the Islamic Education Curriculum and to identify their theoretical and practical implications. Using a qualitative descriptive approach, the research draws on an extensive literature review of classical and contemporary Islamic scholarship, peer-reviewed studies, and national education policies. Thematic analysis highlights key obstacles, including limited educator competence, gender-biased learning materials, and insufficient institutional support, while identifying strategies such as curriculum redesign, gender-sensitive pedagogy, and the effective use of digital and traditional media to challenge stereotypes. The findings reveal that integrating gender values requires not only curricular reform but also a broader epistemological transformation within Islamic education. This study proposes a multidimensional framework for gender-responsive curriculum development. It offers evidence-based recommendations for policymakers, educators, and curriculum developers to promote gender equity across Islamic educational settings.